Endothelial function and dysfunction: Impact of metformin - Nafisa, Asma; Gray, Susan G.; Cao, Yingnan; Wang, Tinghuai; Xu, Suowen; Wattoo, Feroza H.; Barras, Michael; Cohen, Neale; Kamato, Danielle; Little, Peter J. (Pharmacology & therapeutics (Oxford), 2018)
Cardiovascular and metabolic diseases remain the leading cause of morbidity and mortality worldwide. Endothelial dysfunction is a key player in the initiation and progression of cardiovascular and metabolic diseases. Current evidence suggests that the anti-diabetic drug metformin improves insulin resistance and protects against endothelial dysfunction in the vasculature. Hereby, we provide a timely review on the protective effects and molecular mechanisms of metformin in preventing endothelial dysfunction and cardiovascular and metabolic diseases.